1992
DOI: 10.1111/j.1365-2761.1992.tb00678.x
|View full text |Cite
|
Sign up to set email alerts
|

Reservoir hosts and new clupeoid host records for the myoliquefactive myxosporean parasite Kudoa thyrsites (Gilchrist)

Abstract: The myxosporean parasite Kudoa thyrsites (Gilehrist) is well reeognised as a eause of flesh liquefaction post-mortem in several fishes from both hemispheres. The observation of this condition in cultured mahi mahi, Corvphaena hippurus L., in Western Australia ied us to seareh for possible reservoirs of infection amongst the abundant clupeoid fishes of the area. Prevalent and severe infeetions were found in Sardinops sagax neopdchardus (Steindaehner), which we eonsider to be a major reservoir host for K. thyrsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 16 publications
3
26
1
Order By: Relevance
“…Whitaker & Kent (1991), and Barja & Toranzo (1993) isolated Kudoa thyrsites from Atlantic salmon with poor flesh quality. This myxosporean parasite has been associated with post harvest autolysis in other species of marine fishes (Patashnik & Groninger 1964, Langdon et al 1992. Several research groups have found the intensity of infection with Kudoa sp.…”
Section: Introductionmentioning
confidence: 99%
“…Whitaker & Kent (1991), and Barja & Toranzo (1993) isolated Kudoa thyrsites from Atlantic salmon with poor flesh quality. This myxosporean parasite has been associated with post harvest autolysis in other species of marine fishes (Patashnik & Groninger 1964, Langdon et al 1992. Several research groups have found the intensity of infection with Kudoa sp.…”
Section: Introductionmentioning
confidence: 99%
“…Some species are a real danger to cultured stocks, e.g. Sphaerospora testicularis decreases the reproduction rate of sea bass either by destroying the germinative tissue (SitjaBobadilla & Alvarez-Pelli.tero 3.993b) or by feedin.g on spermatozoa (Sitja-Bobadilla & Alvarez-Pellitero 1993e); some Kudoa infections can detract from the marketability of fish products, altho.ugh there is n.o human health risk (see Langdon et al 1992); this could also be the case for the Sphaerospora-like infection in sea bream. Other Myxosporea infections, with no clin-ical signs or serious mortalities, but clear h~stopatho-logical damage, can become a potential threat under stress conditions or may immunodepress the host, hence favouring the entrance and establishment of other pathogens.…”
Section: Resultsmentioning
confidence: 99%
“…This has been suggested for yellowtail infected with Kudoa amamiensis, since coral fish from the same area were also found parasitized by trophozoltes of the parasite. Also several clupeoid fish from Australian waters could be the source of K. thyrsites for cultured Coryphaena hypurus (Langdon et al 1992), and the usual hosts of Kudoa spp. could transmit the parasite to certain salmonids, with subsequent implica.tions for salmon stocks.…”
Section: Zschokkella Sp Myxosporoses Due To Multivalvulidamentioning
confidence: 99%
“…Kudoa thyrsites has been described from 35 fish species from several families around the world, e.g., pen-cultured Atlantic salmon (Salmo salar) and wild-caught flatfish (Paralichthys adspersus) from Chile (Castro and Burgos, 1996). In Japanese waters, three wild host species, Japanese anchovy (Engraulis japonicus), flying fish (Cypsilurus ago) and dolphin fish (Coryphaena hippurus) have been reported to be parasitized by K. thyrsites (Matsumoto, 1963;Langdon et al, 1992). The present study is the first report of K. thyrsites from farmed fish in Japan, implying that K. thyrsites infection may be a potential threat not only to Japanese flounder culture but to other fish species culture in Japan, due to the parasite's broad host range.…”
Section: Discussionmentioning
confidence: 99%
“…The worldwide distribution of K. thyrsites sug gests that the alternate host is a cosmopolitan species of some invertebrate worms. Langdon et al (1992) also suggested that the abundance of several wild fish acting as natural reservoirs of infection contributes to the epi zootics of K. thyrsites in certain locations. In designing the management and control strategies for the Kudoa infections, it is of primary importance to elucidate the life cycles and to determine the infectious stage to fish hosts.…”
Section: Discussionmentioning
confidence: 99%